'Superficial' anastomoses in monochorionic placentas are not always superficial. Issue 9 (September 2015) - Zhao, D.P.; Dang, Q.; Haak, M.C.; Middeldorp, J.M.; Klumper, F.J.C.M.; Oepkes, D.; Lopriore, E.
Abstract Arterioarterial (AA) and venovenous (VV) anastomoses in monochorionic (MC) placentas lie on the placental surface and are termed as superficial anastomoses. The purpose of this study is to report the occurrence of an atypical form of superficial anastomoses which are partially hidden. Partially-hidden superficial anastomoses were defined as vascular anastomoses without visible direct connection on placental surface but with clear mixing of dye after colored dye injection. With analyzing 270 MC placentas, we found a prevalence of partially-hidden AA and VV anastomose of 3% and 5%, respectively. In conclusion, partially-hidden superficial anastomose are not infrequent in MC placentas.